PERSEPSI GURU DAN PERANANNYA DALAM PENCEGAHAN HIV/AIDS PADA SISWA SMA DI KOTA PONTIANAK - , Budi Suryana; , dr. Ova Emillia, M.Med.Ed, SpOG., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Health promotion in increasing awareness through education sector is one way in HIV/AIDS prevention among adolescence, because the school could reach their students in mass number to conveying information, thus the teacherâs role in HIV/AIDS prevention become very important. As an information messenger, the teacher ought to had good understanding, because teacher was needed as key agent for their students in responding HIV/AIDS problem in the school area. Objectives: To knowing the correlation between teacherâs perception and their role in HIV/AIDS prevention in students of Senior High School in Pontianak Municipality. Methods: This was observational study by cross sectional design and was supported by qualitative data through indepth interview. The respondents were teachers and the students, analysis unit were 8 Senior High School based on school standard category. Total were 400 respondents, consist of 200 teachers and 200 students, and was obtained by stratified random sampling. Data analysis used Rank Spearman correlation, with significance level p< 0.05. Results: The teachers had important role in HIV/AIDS prevention with the percentage of 50.5%, had good perception was 53.5% and had good knowledge was 50.0%. There was positive correlation between perception and knowledge to teacherâs role in HIV/AIDS prevention. This means that more positive the teacherâs perception on HIV/AIDS, the higher their role in HIV/AIDS prevention. The higher the teacherâs knowledge on HIV/AIDS, the higher their role in HIV/AIDS prevention among students of Senior High School in Pontianak Municipality. Conclusion: Good knowledge and perception on HIV/AIDS could increasing the teacherâs role in HIV/AIDS prevention in the students, thus it was important for the teacher as information messenger had good understanding, with interactive and innovative learning technique. .